Peningkatan kesadaran bela negara dan kesiapsiagaan dalam menghadapi ancaman bagi anggota Brimob - Rahayu, Yayuk Muji; Akhirudin, Akhirudin (Penamas: Journal of Community Service, 2025)
National security is crucial in maintaining state stability, where the Mobile Brigade (Brimob) has a strategic role as the frontline in dealing with various threats. However, there are still challenges in increasing state defense awareness and readiness of Brimob members. This community service program aims to improve the understanding, skills, and preparedness of Brimob members in facing various forms of physical and non-physical threats. This activity was carried out through lecture methods, interactive discussions, and field simulations carried out at Battalion A Regiment II Pelopor Troops Headquarters, Pamulang, South Tangerang. The results showed increased Brimob members’ understanding of the concept of state defense, readiness to face emergencies, and crisis management skills. In addition, this program also helped strengthen the relationship between Brimob and the community in terms of maintaining security and safety. With this activity, it is hoped that Brimob members will become more professional in carrying out their duties and be better prepared to face future security challenges.